Exploration of Functional Properties and Applications of Probiotic Lactic Acid Bacteria in Fermented Milk Products: A Literature Review - Putri Dian Wulansari; Nurul Fransiska; Nurul Mukminah; Rifda Naufalin (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2026)
Background: Probiotic lactic acid bacteria (LAB) in fermented milk products have attracted considerable attention due to their ability to offer diverse health benefits while simultaneously improving product quality. Comprehensive exploration of the functional properties and applications of probiotic LAB is still needed to meet the evolving demands of the dairy industry. Objective: This study aims to analyze and evaluate the functional properties, mechanisms of action, and applications of probiotic lactic acid bacteria in various fermented milk products through a comprehensive literature review approach. Methods: A structured literature review was conducted by collecting articles from Scopus, PubMed, and Google Scholar databases using keywords